Bacterial cellulose as a potential hard gelatin capsule - Norliza Abd. Rahman,; Nur Syafiqah Kamarudin,; Faezah Esa,; Mohd Sahaid Kalil,; Siti Kartom Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Matured coconut water is considered as an industrial waste where about 5.3m3 of this solution was discarded everyday especially in the coconut processing industry. An improper disposal process can cause environmental pollution especially to nearest river of processing industry. Despite all the advantages of bacterial cellulose (BC) over plant cellulose, its production is relatively expensive process primarily due to the low productivity and expensive culture medium. Thus, coconut water can be used as a medium for fermentation bacterial cellulose and the production cost can be reduced up to 50 to 60%. Acetobacter xylinum 0416 is often used in industry because they can be produced large quantity of BC. There are many applications of BC in industries such as in the food industry, pharmaceutical industry, textiles and etc. However, this study only focuses on the characteristics of hard gelatin capsule (pharmaceutical industry) and BC. This is because, in market there are about 80-90% hard gelatin capsule are non-halal and this situation cause very high demand of halal hard gelatin capsule especially in Islamic countries. This study focus on determination of optimum condition for BC production by manipulation of variable with a certain pH range which is (4-6), the incubator temperature (28-32°C), and time of fermentation (3-7 days). Comparison of BC and hard gelatin capsule properties were made through FESEM, XRD and FTIR analysis. Study found that optimum BC was obtained about 2.28 g/L at 32°C, in pH4 for 7 days fermentation period.